Case study: bench turnover best practice and pit wall remediation at the Newmont Boddington Gold mine - Powell, C.L.; Brockhurst, N.; Wemmers, C.; Torombe, M.; Eames, E.; O.'Callaghan, D.; Findlay, S.; Franks, G.; Ubaid, Z.; Lopez, A. (SSIM 2021: Second International Slope Stability in Mining, 2021)
The Newmont Boddington Gold (NBG) mine excavates over 90 Mt of rock from its open pit operation every year. The pits are mined out in 12 m flitches to form 36 m high composite slope benches with top/middle/bottom flitch batter angles of 75/90/90°. Approximately two benches are mined out of operating pits per annum resulting in kilometres of exposed pit walls. The primary objective of pit development work is to ensure personnel are provided with safe working areas. NBG has some of the steepest pit walls in the industry; therefore, much effort is put into wall evaluation, scaling, and where required, remedial works. This case study presents and illustrates the methods and techniques used at the Boddington Gold mine during bench turnover (BTO) works, how pit walls are evaluated and approved, and what pit wall remedial works are sometimes required to ensure a safe pit. Remedial works are undertaken either during or after BTO work and can involve accessing historic areas of pit wall. At Boddington, BTO works are guided by the geotechnical team and consist of mechanical scaling using an excavator, followed by additional scaling using a dedicated in-pit rock breaker, hydroscaling, and chaining of the crest using either a dozer or an excavator to drag the chain. Wall evaluation includes structural assessment and for the purposes of BTO completion is generally performed through visual observation by geotechnical and operations focused work groups. Documentation of completion and accountability for completing tasks is established using a multimedia based approach including in field reporting using FastField Forms™ and the workflow planning and accountability software Trello™.Remedial works are sometimes required to address particular areas of concern in the pit. Remedial works at Boddington can include additional scaling, removal of sections of pit wall, cable bolting, installation of rockfall mesh, and construction of rockfall fences. This paper discusses how works are safely planned, delivered and documented.